Utilizing Cooperative Learning in Islamic College Students’ Classroom - Abdul Gafur Marzuki (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
ABSTRACT The research aims at utilizing cooperative learning in teaching reading skill for Islamic college students. The research was classroom action research which was conducted in two cycles where each cycle consisted of planning, implementation, observation and reflection. The subject were taken from PAI 5 which contained 30 students. The data of this research were obtained from the test, observation checklist, and field notes. The findings of research showed that cooperative learning was effective in developing students’ reading skill. The findings revealed that there were nineteen students who achieved the minimum criteria of achievement in cycle 1, which percentage was 63.3%. In cycle 2, it was found that there were twenty five students who achieved the minimum criteria of achievement, which percentage increased to 83.3%. Both of the classical and individual achievements have met the criteria of success. Besides, students were active in joining classroom activities and completing their classroom tasks. Therefore, it can be concluded that the cooperative learning was effective to develop the students’ reading skill. ABSTRAK Penelitian ini bertujuan untuk memanfaatkan pembelajaran kooperatif dalam pembelajaran keterampilan membaca mahasiswa di perguruan tinggi Islam. Penelitian ini merupakan penelitian tindakan kelas yang dilakukan dalam dua siklus dimana setiap siklus terdiri dari perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian diambil dari kelas PAI 5 yang terdiri dari 30 mahasiswa. Data penelitian ini diperoleh dari hasil tes, lembar observasi, dan catatan lapangan. Temuan penelitian menunjukkan bahwa pembelajaran kooperatif efektif dalam mengembangkan keterampilan membaca mahasiswa. Temuan menunjukkan bahwa ada sembilan belas mahasiswa yang mencapai kriteria pencapaian minimal pada siklus 1, dengan persentase 63,3%. Pada siklus 2, ditemukan bahwa ada dua puluh lima mahasiswa yang mencapai kriteria pencapaian minimum dengan persentase 83,3%. Persentase klasik dan individual telah memenuhi kriteria keberhasilan. Selain itu, mahasiswa aktif mengikuti kegiatan kelas dan menyelesaikan tugas kelas mereka. Oleh karena itu, dapat disimpulkan bahwa pembelajaran kooperatif efektif untuk mengembangkan keterampilan membaca mahasiswa. How to Cite: Marzuki, A., G. (2016). Utilizing Cooperative Learning in Islamic College Students’ Classroom. IJEE (Indonesian Journal of English Education), 3(2), 123-139 doi:10.15408/ijee.v3i2.5528. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i2.5528